INLAND FISHERIES DEVELOPMENT IN THE ISLAND ECOSYSTEM OF A & N ISLANDS - DAS, BASANTA KUMAR; DAS, ARCHAN KANTI; MOHANTY, BIMAL PRASANNA; CHANDRASEKHAR, J.; HAMJA, C.; TALUKDAR, S. K.; SAR, UTPAL KUMAR (Journal of the Inland Fisheries Society of India, 2021)
The Andaman &Nicobar Islands consist of 352 islands, 220 islets and rocks covering a distance of almost 800 km over North - South, with a coastline of 1962 km. The island has a very large ichthyofaunal diversity owing to the varied marine habitats. So far around 1400 fish species has been recorded from the island out of which 400 species are of commercial significance as food fishes (Rao 2009; Rajan, Sreeraj and Immanuel 2013). Along with marine resources, the island harbors inland open water systems like lakes, canals and large ponds which have not been optimally utilized for fisheries so far. To assess the scope of enhancing the fish production from the inland open water resources, a team of Scientists from ICAR-CIFRI visited the islands on invitation from the Department of Fisheries, Andaman and Nicobar Administration during 02-06 May, 2017.